Empty substrate‐integrated waveguide phase inverter in millimetre‐wave band application. Issue 8 (1st April 2020) - Peng, Hao; Zhao, Faju; Tatu, Serioja Ovidiu; Dong, Jun; Yang, Tao
Abstract : In this Letter, a novel empty substrate‐integrated waveguide (ESIW) phase inverter (PI) applied in millimetre‐wave has been proposed. ESIW PI, based on the structural symmetry design, is made of four parts: top cover, middle layer, ESIW PCB, and bottom layer. Owing to the reversed‐phase transmission channel, the phase difference between the two outputs is absolutely equal to 180°. The simulation and measurement results are in a good agreement. In the entire Ka band, the return losses, insertion losses and amplitude imbalance of ESIW PI are better than 12.7, 2.66, and 0.64 dB ± 0.6 dB, respectively. Besides, the phase difference is within 180.5° ± 2.9° in the same frequency band. In addition, the input and output ports are located in the identical circuit plane, which is easy to integrate with other devices and components.